2022
DOI: 10.1186/s12920-022-01340-7
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis reveals the potential value of inflammatory response genes in the prognosis, immunity, and drug sensitivity of lung adenocarcinoma

Abstract: Background Although the relationship between inflammatory response and tumor has been gradually recognized, the potential implications of of inflammatory response genes in lung adenocarcinoma (LUAD) remains poorly investigated. Methods RNA sequencing and clinical data were obtained from multiple independent datasets (GSE29013, GSE30219, GSE31210, GSE37745, GSE42127, GSE50081, GSE68465, GSE72094, TCGA and GTEx). Unsupervised clustering analysis was used to identify diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 98 publications
0
0
1
Order By: Relevance
“…The 1-, 2- and 3-year area under the curve (AUC) values reached 0.752, 0.728, and 0.731 in our signature, respectively, whereas the 1-, 2- and 3-year AUC values in Song et al’s study was 0.719, 0.705 and 0.701. Thus, the predicting ability of our prognostic model was higher than that of their study [ 18 ]. Research has shown that hypoxia-related, ferroptosis-related, and immune-related gene signatures predict OS at three years, similar to our results [ 19 , 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 64%
“…The 1-, 2- and 3-year area under the curve (AUC) values reached 0.752, 0.728, and 0.731 in our signature, respectively, whereas the 1-, 2- and 3-year AUC values in Song et al’s study was 0.719, 0.705 and 0.701. Thus, the predicting ability of our prognostic model was higher than that of their study [ 18 ]. Research has shown that hypoxia-related, ferroptosis-related, and immune-related gene signatures predict OS at three years, similar to our results [ 19 , 20 , 21 ].…”
Section: Discussioncontrasting
confidence: 64%
“…The dysregulation of GNAI3 has been linked to malignancies. Its aberrant expression or genetic mutations have been detected in different cancer types, including breast cancer, colorectal cancer, and lung adenocarcinoma [23]. In these contexts, its dysregulation can impact tumor growth, metastasis, and response to therapy.…”
Section: Introductionmentioning
confidence: 99%